2009
DOI: 10.1007/s11661-009-9789-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Parameters Influencing the Quench-Aging Behavior of Ultra-Low-Carbon Steels

Abstract: The influence of the annealing temperature and of the grain size on the quench-aging behavior of ultra-low-carbon (ULC) steels was investigated by thermoelectric power measurements (TEPs) and mechanical testing. The TEP technique showed that the quench aging of ULC steels occurs in two distinct stages: (1) the segregation of carbon atoms to the grain boundaries and (2) the precipitation of iron carbides. It was suggested that the degree of grain boundary coverage by the carbon atoms resulting from the annealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The lower yield point then represents the stress needed to move dislocations that have been freed from their atmospheres. This could be attributed to the ferrite grain coarsening and diffusion of carbon atoms to grain boundaries as already described as Cottrell-Bilby atmosphere in iron-based alloys [34]. …”
Section: Mechanical Propertiesmentioning
confidence: 67%
See 1 more Smart Citation
“…The lower yield point then represents the stress needed to move dislocations that have been freed from their atmospheres. This could be attributed to the ferrite grain coarsening and diffusion of carbon atoms to grain boundaries as already described as Cottrell-Bilby atmosphere in iron-based alloys [34]. …”
Section: Mechanical Propertiesmentioning
confidence: 67%
“…In Fe and Fe-based alloys, this phenomenon is due to interstitial solid solution generally formed by carbon at room temperature [34]. Deformation takes place by movement of dislocations, but the atmosphere of solute atoms surrounding dislocations anchors the dislocations thereby restraining their motion.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Among the four steels, the ferrite grain size decreased with an increase in carbon content. Previous studies [9,25] have shown that decreasing the grain size favors the occurrence of the yield-drop phenomenon. If the effect of grain size is strong enough, the 0.3C steel, whose ferrite grain size is the smallest, should have the yield-drop phenomenon.…”
Section: Yield-point Phenomenonmentioning
confidence: 87%
“…During the annealing at 950 • C, the interstitial atoms could segregate along grain boundaries [24]. In the holding at 750 • C, these grainboundary segregated interstitials may have reacted with Nb to form fine Nb(C, N) precipitates, with Fig.…”
Section: Discussionmentioning
confidence: 99%